Increased airway iron parameters and risk for exacerbation in COPD: an analysis from SPIROMICS - Cloonan, Suzanne (My University, 2020)
Levels of iron and iron-related proteins including ferritin are higher in the lung tissue and lavage fluid of individuals with chronic obstructive pulmonary disease (COPD), when compared to healthy controls. Whether more iron in the extracellular milieu of the lung associates with distinct clinical phenotypes of COPD, including increased exacerbation susceptibility, is unknown. We measured iron and ferritin levels in the bronchoalveolar lavage fluid (BALF) of participants enrolled in the SubPopulations and InteRmediate Outcome Measures In COPD (SPIROMICS) bronchoscopy sub-study (n = 195). BALF Iron parameters were compared to systemic markers of iron availability and tested for association with FEV1 % predicted and exacerbation frequency. Exacerbations were modelled using a zero-inflated negative binomial model using age, sex, smoking, and FEV1 % predicted as clinical covariates. BALF iron and ferritin were higher in participants with COPD and in smokers without COPD when compared to non-smoker control participants but did not correlate with systemic iron markers. BALF ferritin and iron were elevated in participants who had COPD exacerbations, with a 2-fold increase in BALF ferritin and iron conveying a 24% and 2-fold increase in exacerbation risk, respectively. Similar associations were not observed with plasma ferritin. Increased airway iron levels may be representative of a distinct pathobiological phenomenon that results in more frequent COPD exacerbation events, contributing to disease progression in these individuals.
PUBLISHED
Keywords: COPD; Iron; Bronchoalveolar lavage fluid; Ferritin